Cognitive Behavioural Therapy for Chronic Pain Management: A Narrative Review - Liang, Carolyn; Ahmad, Mahadir (IIUM Medical Journal Malaysia, 2022)
Chronic pain is disabling and impacts an individual’s psychosocial and functioning in multiple areas. Cognitive Behavioural Therapy (CBT) appears to be one of the psychotherapies that has good potential of prominent efficacy in managing chronic pain. This narrative review aims to provide the necessary information and latest development on the delivery, results efficacy and barriers of CBT in chronic pain management. A search was conducted at Pubmed and Web of Science in April 2021 yielding a total of 251 articles. After careful screening and filtration, a total of 21 articles was selected for this review. Of these 21 articles, CBT was observed to be commonly delivered through online, which helped to preserving cost, promoting adherence, having good efficacy and also safer during the time of the Covid-19 pandemic. Most of the articles showed significant efficacy of CBT in chronic pain management. In order to improve CBT for better efficacy, understanding and consideration towards mediators that affect pain outcome and barriers in implementation are crucial in developing modules in CBT for chronic pain management. As such, CBT can be improved by integrating customised components in the modules to target mediators specifically, and training can be provided for psychotherapist to combat the barrier of online communication and time management. For future research, direction can be focused on development of CBT modules that are specific to chronic pain management.